(untitled) (Academia Journal of Medicine, 2025)
Diabetic retinopathy (DR) is one of the most common microvascular complications of diabetes mellitus and a leading cause of preventable blindness globally. Despite advancements in modern ophthalmology, current treatment options are often invasive and expensive, leading to an increased interest in complementary and alternative therapies, especially Ayurveda.